Indikator Ilmu Pengetahuan dan Teknologi Bagi Pembangunan - M. Anandakrishnan; Hiroko Morita-Lou; Bambang Ismadi (Penterjemah); Putut Budijanto (Penterjemah) (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 1991)
-